Education in the wetlands and wetlands in the education: a case of contextualizing primary/basic education in Tanzania - Hogan, Alice Rosemary (Rhodes University, Faculty of Education, Department of Education, 2008)
This dissertation describes an action research case study carried out at a sub-village school at Nyamakurukuru, Utete, Rufiji District, Tanzania. The study was a fully independent research activity funded and led by a female Irish environmental and community specialist who has fifteen years experience of working in rural Tanzania, five of which were in Rufiji District. The aim of the action research was to engage a community of villagers, teachers, students and district officers in a participatory process to adapt a module of a school curriculum to the local context, and teach it in order to describe one way in which contextualization, using local and indigenous knowledge and active discovery teaching-learning processes, can be done. The major research question, which I wished to answer for one specific case, was: Does integrating local environmental cultural knowledge into formal schooling contribute to curriculum relevance? If so, in what way? This document describes the background and context of the research, the motivation and the theoretical basis for the work, the methodology and methods, and the action research process itself. The results are interpreted and discussed in the light of current theoretical perspectives on education and environmental education. The main findings within the case are that: Contextualization improved relevance of education and thus its quality by: "¢ breaking through traditional frames/barriers between teachers and students, students and elders and community and teachers, "¢ allowing formal education to take place outside of the school, "¢ necessitating a change in pedagogy1 to more learner-centered, discovery methods, "¢ allowing indigenous knowledge to come into the classroom, "¢ stimulating creativity and increased confidence, and "¢ bringing local socio-political environmental issues into the classroom. This study provides a case example of how education processes, when engaging local cultural knowledge, can improve the relevance, and thus an aspect of the quality of teaching and learning in school-community contexts, while providing a conduit for integrating environmental education into the formal school curriculum. It provides insights into the key issue of relevance which currently faces educators of children in wetlands in Tanzania. Recommendations were made for the case studied and may be useful beyond the boundaries of the case: "¢ Give more explicit government policy and strategic support for community involvement in educational content"“epistemologies and pedagogies. "¢ Weaken framing (hierarchical power positions) to encourage greater partnership between school, home and community to improve relevance. "¢ Investigate the provision of education beyond schools. "¢ Provide practical teacher and community training on use of learner-centered, discovery and active pedagogies. "¢ Provide teacher and community education on biodiversity and the environment. "¢ Provide relevant reference texts and research data on the ecology, biodiversity, vegetation, hydrology, agriculture, sociology, history and other relevant subjects. "¢ Officially nurture a culture that learning should be enjoyable. "¢ Allow the curriculum freedom, in these times of increasing risk for rural tropical wetland communities, to make the curriculum fit the local issues rather than vice versa. "¢ Nurture critical analysis of the curriculum in local pedagogic discourse i.e., at the local contextualization level of the home, community and school.
Keywords: Education -- Tanzania; Environmental education -- Tanzania; Education, Rural -- Tanzania; Education -- Curricula -- Tanzania; Community and school -- Tanzania